Learning Media Development for Continuously Variable Transmission Automatic Transmission System Subjects on Motorcycles - Lapisa, Remon; Azhari, Nevil (IJECA (International Journal of Education and Curriculum Application), 2021)
Teaching aids that have similarities to tools are actually very helpful in learning. In improving students' understanding, learning media is needed, namely a simulator. This study aims to design a Continuously Variable Transmission (CVT) simulator with validity, practicality and effectiveness, useful to be used as a medium of learning in schools in the subject of automatic transmission systems. The type of research used is Research and Development (R&D) with 4-D model development procedures. This research consists of four stages, namely: Define, Design, Develop, and Disseminate. The subjects used were students of SMKN 1 Koto Baru Dharmasraya, the technical analysis of the data used was technical analysis from experts by looking at the validity, practicality and effectiveness of the simulator. To see the difference between the average score of learning scores before and after using a simulator with Gain Score and Standard Deviation. The results showed that the simulator met the principle of relevance from expert judgment with a level of 0.81 which was declared a valid category, on practicality based on the teacher's response it was declared practical with a value of 87.33% and student responses with a value of 92.42%. The effectiveness of the tool is declared effective. On the results of the pretest with an average score of 56.00%, the results of the posttest with an average score of 73.00%, on the N-gain the overall average of students is 0.37 and on the standard deviation seen from the N-gain of 0.12. Based on the development of this media, it can be concluded that the simulator is valid, practical and effective in learning at school